SMART Feedback: Improving the Effectiveness of Metacognitive-Based Learning Applications - Widiana, I Wayan; Ida Bagus Gede Surya Abadi; Anak Agung Istri Dewi Adhi Utami (MIMBAR PGSD Undiksha, 2024)
Many students still have difficulty in developing metacognitive skills during the learning process. This is due to the lack of learning media that can provide appropriate feedback, as well as the absence of applications that support metacognitive-based learning. The purpose of this study is to develop the SMART Feedback application in metacognitive-based learning. This type of research is Research and Development (R&D) using the ADDIE development model. The subjects of this study consisted of 2 media experts, 2 material experts, and 2 learning experts. The subjects of the research trial included 1 teacher/practitioner, 3 students (individual trials), and 6 students (small group trials). Data collection methods used observation, interviews, questionnaires, and tests. The instruments used were questionnaire sheets and test questions. The data analysis techniques used in this study were qualitative descriptive analysis, quantitative descriptive analysis, and inferential statistics. The results showed that the assessment of media experts was 94% (very valid), material experts 91% (very valid), and learning experts 93% (very valid). The results of the individual trial obtained a score of 94% (very practical), the small group trial was 95% (very practical), and the teacher's assessment reached 92% (very practical). The results of the effectiveness test showed an increase in student learning outcomes after using the SMART Feedback application. It was concluded that the SMART Feedback application is feasible to use in learning and is effective in improving students' metacognitive skills.